Carbon consumption patterns of emerging middle classes - Babette Never; Jose Ramon Albert; Hanna Fuhrmann; Sebastian Gsell; Miguel Jaramillo; Sascha Kuhn; Bernardin Senadza (Deutsches Institut für Entwicklungspolitik (DIE), 2020)
As households move out of poverty, spending patterns change. This is good news from a development perspective, but changing consumer behaviour may imply substantially more carbon emissions. The lifestyle choices of the emerging middle classes are key, now and in the future. This paper explores the consumption patterns of the emerging middle classes and their carbon intensity, using unique micro data from household surveys conducted in Ghana, Peru and the Philippines. We find that carbon-intensive consumption increases with wealth in all three countries, and most sharply from the fourth to the fifth middle-class quintile due to changes in travel behaviour, asset ownership and use. In Peru, this shift in the upper-middle-class quintiles translates to annual incomes of roughly USD 11,000-17,000 purchasing power parity. Environmental knowledge and concern are fairly evenly spread at mid- to high levels and do lead to more easy-entry sustainable behaviours, but they do not decrease the level of carbon emissions. To some extent, a knowledge/concern-action gap exists. In our study, social status matters less than the literature claims. Our results have two implications. First, the differentiations between developing/developed countries in the global climate debate may be outdated: It is about being part of the global middle classes or not. Second, a positive spillover from existing easy-entry sustainable behaviours to a change in carbon-intensive consumption patterns needs policy support.
Keywords: 330; Treibhausgas-Emissionen; Energiekonsum; Mittelschicht; Ghana; Peru; Philippinen